Students’ Innovativeness in Developing Business: An Empirical Study of Kolb’s Experiential Learning on Entrepreneurship Course - Sukardi Sukardi; Baik Nilawati Astini; Nursaptini Nursaptini (Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This study investigates the efficacy and effects of Kolb's experiential learning (EL) model and students' scientific field groups on their innovativeness in business development. (1) Humanities and Social Science, and (2) Science and Technology are the scientific field groups. A quasi-experimental quantitative approach with a 2 x 2 factorial design was used in this study. This study's sample encompassed active Faculty of Teacher Training and Education of the University of Mataram enrolling for entrepreneurship courses which were taken using random sampling after commensuration processes. The data collection instrument used to collect data on students' innovativeness is a project-based assessment based on indicators of innovativeness in developing products and digital marketing. The results of the instrument test fulfilled the validity and reliability requirement. All data were analyzed statistically by descriptive statistics and comparative analysis using the ANOVA test, which was preceded by an analysis requirement test. The study results showed an interaction effect of the EL model and students' scientific field on students' innovativeness. In addition, Kolb's EL model also directly affects students' innovativeness, while the scientific field group does not. Nevertheless, the data showed that the Science and Technology group innovates better than the others. The theoretical implication of this study was that EL has a strong theoretical framework for entrepreneurial learning, so it needs to be expanded through further studies.